Prevalence of mycoplasma pneumoniae in patients with community-acquired pneumonia at Tishreen University Hospital in Lattakia - يازجي هيثم; حجازية مالك; دويبة أسامة (Latakia University Journal -Medical Sciences Series, 2021)
Mycoplasma pneumoniae is one of the most common causes of community acquired pneumonia, which is considered an important common disease that may lead to death. The study aims to determine the prevalence of mycoplasma pneumoniae in community-acquired pneumonia patients by investigating IgM antibodies by the ELISA method in adult patients diagnosed with community acquired pneumonia at Tishreen University Hospital in Latakia A cross-sectional study included 90 patients diagnosed with radiologically and clinically acquired community-acquired pneumonia, tuberculosis patients, immuno compromised and hospital pneumonia patients were excluded. Patients were distributed between 55 males and 35 females, with ages ranging from 15-86 years. The prevalence of mycoplasma pneumoniae in community-acquired pneumonia patients was 5.6% of the studied sample The study did not show a correlation between the patient’s age, gender, and CRP value, with the positive test, i.e. the presence of Mycoplasma pneumoniae. The study showed that mycoplasma pneumoniae is an important cause of community-acquired pneumonia, and that the test for mycoplasma pneumoniae antibodies is a good and fast test for detecting the presence of Mycoplasma pneumoniae that can be used routinely and benefit from the diagnosis of pneumonia caused by mycoplasma pneumoniae, which helps in the appropriate selection of antibiotics and thus reduce the random use of these antibiotics